Rule based ETL (RETL) approach for GEO spatial data warehouse - Nordin, Norhaira; Yasin, Azman; Omar, Mazni (2014)
This paper presents the use of Service Oriented Architecture (SOA) for integrating multi source heterogeneous geospatial data in order to facilitate geospatial data warehouse. In this study, Real Based ETL (RETL) concept is adapted in order to extract, transform and load data from a variety of heterogeneous data sources. ETL will transform data to schematic format and loading data into the Geo spatial data warehouse.By using a rule-based technique, the distribution of parallel ETL pipeline will enhance and perform more efficient in large scale of data and overcome data bottleneck and performance overhead. This can ease the disaster management and enables planners to monitor disaster emergency response in an efficient manner.